Jefferson's sons : a founding father's secret children - Bradley, Kimberly Brubaker (New York : Puffin Books, 2013)
A fictionalized look at the last twenty years of Thomas Jefferson's life at Monticello through the eyes of three of his slaves, two of whom were his sons by his slave, Sally Hemings.
Originally published: New York : Dial Books for Young Readers, 2011.
Includes reading group discussion guide.
Sequoyah Nominee MS 2014
Keywords: Jefferson, Thomas, -- 1743-1826 -- Fiction; Hemings, Sally -- Fiction; Slavery -- Fiction; African Americans -- Fiction; Monticello (Va.) -- Fiction; Virginia -- History -- Fiction